Clifford the big red dog : the big itch - Bridwell, Norman; Cuddy, Robbin; Perrotta, Anne-Marie.; Schultz, Tean. (New York : Scholastic, 2003)
Clifford develops a terrible itch but tries to hide it from Emily Elizabeth so he will not have to go to the veterinarian.
"Based on the Scholastic book series 'Clifford the big red dog' by Norman Bridwell."
"From the television script 'An itchy patch' by Anne-Marie Perrotta and Tean Schultz."
"Watch on PBS Kids"--Cover.
K-3.
Keywords: Clifford (Fictitious character : Bridwell); Dogs -- Fiction; Juvenile Fiction; Veterinarians -- Fiction